Legislate with the citizenship: A view from Open Parliament in México - Rojas Aguilar, Joyce Pamela; Carrillo Huerta, Mario Miguel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
It is possible to appreciate a several series of factors that have been weakened the representative democracy, specifically, the legislative activity, which encounters challenges that add to the problem of the research. It’s in the context of Open Parliament that citizen participation becomes scientifically relevant within the framework of the theory of representative democracy. The following research question will be answered through mixed methodology: How are democratized spaces generated in the legislative activity of the Open Parliament? This article is a first approach to a PhD research in progress, conclusions will be presented in a following congress of CUICIID.